Hydrolyzable Bio‐Based Bisphenols Enabled by the Tishchenko Reaction for Polyurethane Vitrimers with Closed‐Loop Recyclability - Jiewen Wang; Hongru Qiang; Rong Huang; Dan Zhao; Zihan Tong; Zhen Fan; Jianzhong Du; Yunqing Zhu (Advanced Science)
Abstract Polyurethane (PU) is a cornerstone of modern materials science, yet its reliance on petroleum‐based precursors and the limited recyclability of conventional formulations pose significant environmental challenges. In this study, a fully bio‐based polyurethane vitrimer system is developed enabled by a dual‐function SmI2‐mediated strategy that integrates Tishchenko coupling and phenol deprotection in a single step, simplifying the synthesis of bio‐based bisphenols with 100% atom utilization. These bisphenols introduce hydrolyzable ester bonds, allowing for complete degradation within ≈3 d (representative model), providing an efficient and eco‐friendly end‐of‐life solution. This approach offers a sustainable alternative to conventional bisphenol A (BPA). Moreover, by leveraging the electronic effects of bio‐based bisphenols, the dissociation temperature of phenol‐carbamate bonds can be widely tuned (≈70–120 °C), endowing the resulting Covalent Adaptable Network (CAN) PUs with excellent reprocessability, closed‐loop recyclability, and reconfigurable shape memory capability. Furthermore, the aromatic and ester‐rich structure enhances thermomechanical performance, yielding tensile strengths up to 33 MPa, elongations at break exceeding 400%, and toughness reaching 30 MJ m−3, surpassing most sustainable PUs. This work pioneers a scalable and fully bio‐based PU vitrimer platform with tunable performance, recyclability, and sustainable degradability, offering a compelling alternative to traditional thermosets and thermoplastics for next‐generation green materials.